Jurisprudential characterization of the person infected with the Corona epidemic and the jurisprudential rulings resulting from his disposal in financial compensation contracts: Sale contract as a model - Saleh, Mohamed Atia (Journal of Islamic Sciences, 2021)
This research aims to clarify the jurisprudential characterization of the person infected with the Corona epidemic, and to clarify the jurisprudential provisions resulting from his disposal in the sales contract; This is because the patient may suffer from obsessions that affect his behavior, and the researcher has combined the inductive approach by following the issues related to the topic of research, collecting and categorizing them, and the descriptive approach in terms of mentioning the sayings of the jurists in each issue with its evidence, with mentioning the sayings of the considered schools of jurisprudence, and the discussions on them as possible, and clarifying The most correct, and the reason for the weightingThe researcher came out with results, the most important of which are: The Corona epidemic can be described by what is called jurisprudence as a dreaded disease, selling the person infected with the Corona epidemic if he is not indebted to a foreigner or buying it from him for the same price is valid without the heirs’ permission, whether debtor or not, and it is also true if it is a favoritism of one third or less Pre-emption is established for the partner in the case of the patient selling to an heir or someone else if the sale is made at the same price, pre-emption is established for the intercessor if the purchaser is from the patient by favoritism and the intercessor is foreign, and the option of the condition and the fault of the person suffering from the epidemic is not lost if there is an excuse such as loss of consciousness or the like.
Keywords: Corona epidemic; selling; favoritism; pre-emption; the option of the condition; the option of defect